Therapie der Varikose im Wandel der Zeit - Korsake, K.; Stücker, M.; Reich-Schupke, S. (Phlebologie, 2019)
Insbesondere in den letzten zwei Dekaden hat sich die Therapie der Varikose rasant entwickelt. Es sind zahlreiche neue Therapiemodalitäten hinzugekommen. Während zuvor die operative Therapie der Varikose mittels Cross- und Saphenektomie als Standard galt, empfehlen internationale Leitlinien derzeit primär eine endoluminale Therapie der Varikose mittels endovenöse Laser-, Radiofrequenztherapie oder Sklerosierung (NICE, AVF).Bisher fehlt ein Überblick über die Etablierung der Anwendung dieser neuen Therapieoptionen in Deutschland. In unserer Studie haben wir eine Befragung von Ärzten, deren Einrichtung als Venenkompetenzzentrums zertifiziert sind (Stand 4/2017–149), zu ihrem Vorgehen bei primärer Varikose und Rezidivvarikose vor 20 Jahren, 10 Jahren und heute, durchgeführt.Die Daten zeigen einer zunehmenden Tendenz zur endovenösen Behandlung der Varikose. Die Zahlen der klassischen operativen Therapie sind im untersuchten Kollektiv in den letzten 20 Jahren deutlich gesunken.The therapy of varicose veins has developed rapidly in the last two decade. Numerous new therapy methods have been added. Surgical treatment with crossectomy and saphenectomy has been a gold standard for many years. International guidelines (NICE, AVF) currently recommend endoluminal laser ablation, radiofrequency ablation or sclerotherapy treatment of varicose veins as first line treatment. The extent and establishment of these new techniques in clinical practice in Germany over the last 20 years to today is unknown. Therefore was a survey initiated about the therapy methods for primary varicose veins and recurrent varicose veins 20 years ago, 10 years ago and today. All phlebologists, who work in the certificated vein competence centres in Germany, were included in this study. (According to the German Society of Phlebology and the Professional Association of Phlebologists 149 centres (Stand 4/2017)). The Date from the electronical questionnaires was anonymized and evaluated.These data provide evidence about an increasing trend of endovenous treatment (endovenous laser therapy, endovenous radiofrequency therapy, foam sclerotherapy, etc.) of varicosis in the last two decades. The numbers of classic surgical therapy have dropped significantly in the last 20 years.
Keywords: Varizen; Varizenchirurgie; Lasertherapie; Radiofrequenztherapie